Affordable housing, democratic erosion, and the inevitability of capitalism - McLeay, Colin (New Zealand Sociology, 2022)
Recent New Zealand governments have sought to increase the provision of affordable housing. Responding to a severe home affordability and ownership crisis, National-led Governments in office between 2008 and 2017 implemented initiatives designed to encourage ownership among first-home buyers. State-directed efforts around affordable housing focused on increasing the supply of land for housing and encouraging builders to include affordable housing in their developments. Evidence from New Zealand Parliamentary Debates (Hansard) shows the Housing Accords and Special Housing Areas Act 2013 introduced by a National-led Government reinforced the inevitably of the mechanisms of neoliberal capitalism. Members of Parliament tacitly accepted the worth of market mechanisms and the centrality of capitalism to the provision of affordable housing. This paper identifies ways in which recent state intervention in the affordable housing market was expressive of neoliberal capture of the political process. Parliamentary debates associated with the Housing Accords and Special Housing Areas Act 2013 failed to provide a challenge to the place of the market in the organisation and regulation of the state and society.